Resolving SAP ERP Warehouse Management Module Implementation Issues in a Consumer Goods Company: A Case Study of PT XYZ - Christian Herlando Indra Jaya (AI Society & STMIK Indonesia, 2025)
This study analyzes the challenges associated with the implementation of the Warehouse Management (WM) module in SAP ERP at PT XYZ, a leading FMCG company in Indonesia, and proposes solutions to address them. The implementation of the WM module aims to reduce manual processes and enhance warehouse efficiency, thereby supporting operational success by improving stock data accuracy and integrating business processes. However, the current implementation has not fully met the company’s operational needs. The research adopts a qualitative approach using the Soft Systems Methodology (SSM). Data were collected through interviews with six respondents and operational observations. The analysis focuses on system quality, data quality, organizational culture, and user support to identify existing gaps. The findings reveal several issues, including non-real-time information, stock inaccuracies, reliance on manual processes, and the absence of knowledge management. Recommendations include integrating IoT, developing real-time applications for picking and stock counting, automating replenishment using AI, implementing SAP Analytics Cloud (SAC), and creating a knowledge management system. This study provides practical solutions for similar companies to enhance ERP implementation success, particularly in the Warehouse Management module.